Initiation of Disease-Modifying Therapies in Rheumatoid Arthritis Is Associated With Changes in Blood Pressure. Issue 4 (June 2018) - Baker, Joshua F.; Sauer, Brian; Teng, Chia-Chen; George, Michael; Cannon, Grant W.; Ibrahim, Said; Cannella, Amy; England, Bryant R.; Michaud, Kaleb; Caplan, Liron; Davis, Lisa A.; O'Dell, James; et al.
Abstract : Purpose: This study reports the effect of disease-modifying therapies for rheumatoid arthritis (RA) on systolic and diastolic blood pressure (SBP, DBP) over 6 months and incident hypertension over 3 years in a large administrative database. Methods: We used administrative Veterans Affairs databases to define unique dispensing episodes of methotrexate, leflunomide, sulfasalazine, hydroxychloroquine, tumor necrosis factor inhibitors, and prednisone among patients with RA. Changes in SBP and DBP in the 6 months before disease-modifying antirheumatic drug initiation were compared with changes observed in the 6 months after initiation. The risk of incident hypertension within 3 years (new diagnosis code for hypertension and prescription for antihypertensive) was also assessed. Multivariable models and propensity analyses assessed the impact of confounding by indication. Results: A total of 37, 900 treatment courses in 21, 216 unique patients contributed data. Overall, there were no changes in SBP or DBP in 6 months prior to disease-modifying antirheumatic drug initiation (all P > 0.62). In contrast, there was a decline in SBP (β = −1.08 [−1.32 to −0.85]; P < 0.0001) and DBP (β = −0.48 [−0.62 to −0.33]; P < 0.0001) over the 6 months following initiation. The greatest decline was observed among methotrexate and hydroxychloroquine users. Methotrexate users were 9% more likely to have optimal blood pressure (BP) after 6 months of treatment. Patients treated with leflunomide had increases in BP and a greater risk of incident hypertension compared with patients treated with methotrexate (hazard ratio, 1.53 [1.21–1.91]; P < 0.001). Conclusions: Blood pressure may improve with treatment of RA, particularly with methotrexate or hydroxychloroquine. Leflunomide use, in contrast, is associated with increases in BP and a greater risk of incident hypertension. Abstract : Supplemental digital content is available in the text.